O Judaísmo Encalacrado: mística e religião em A Hora da Estrela, de Clarice Lispector - Silva, Evandro Cesar Cantaria da (2006)
The objective of this work was to demonstrate to the importance and relevancy of the dialogue between literature and religion, concentrating the scope of its research from the relations between the writing of Clarice Lispector and the resonances of a tradition (judaism), although it never was assumed for the author, persists, risk in all its workmanship. Having, the object as research the novel the Hour of the Star, this dissertation sought to understand the drama of the narrative in its play of tensions and identities, in its plurality of headings and references, also signs of deep problem with the religion. Focusing especially on the Macabéa personage, this research sought to probe the references of the personage, its difficulty with words, its failures in meeting of the other (thou) and its social rejection. These problems discloses a serious problem of theological order, demonstrating the mistakes of a society, that established on the prism of the religion and massacres weakkest. The outcome of the book signs possible epiphany, but, disclose in the a failure of the religion and its power to save. Based on the principle themes of the novel, perceive its correspondences with the subject of the religion. From this, based on the contributions of Scholem, it is possible to see how the existential and subjective quandary of the personage approximates the mystic tragedy cabalistic. Besides to perceive the correlations between the text of author and texts of the jewish tradition, in its explicit reference (name of the personage), as well as, in its aspect of search, its form of midrash and the innumerable exegeses and commentaries that it propitiates. The final contribution of the text is to raise an ethical quarrel regarding the theological values of the society, and its profound errors, in light of the life and death of the poor Macabéa, a woman who lived her religion to the limits of her own existence